Effects of Brown Algae (Laminaria japonica) Extract on Growth Performance, Immune Function and Intestinal Health of Largemouth Bass (Micropterus salmoides) - Jiajia Shen; Hongxiang Liu; Mengran Wang; Bo Lu; Ke Ke; Yunyong Wei; Feng Gao; Qiaozhen Wang; Shushi Huang; Yanqun Ma (Animals)
This study used largemouth bass (initial average weight: 33.33 ± 1.8 g) to explore the effects of adding different brown algae extracts to feed on the fish’s growth, immunity and intestinal health. Six groups were set up: a control (Group A), 0.1% sodium alginate (Group B), 0.1% oligotriosaccharide I (Group C), 0.1% oligotriosaccharide II (Group D), 0.2% brown algae powder (Group E) and 0.2% brown algae powder enzymatic product (Group F), with three replicates of 35 fish each, and a 56-day feeding experiment. Results: Compared to Group A, Groups C, D and F had a higher specific growth rate and lower feed coefficient (p < 0.05). Group D had enhanced serum SOD activity; Group F had increased antioxidant enzyme activity and decreased MDA content (p < 0.05). All experimental groups had higher serum LZM levels (p < 0.05), with no IgM difference (p > 0.05). In the intestine, treatment groups had higher α-amylase activity (p < 0.05) and no lipase difference (p > 0.05), and Groups C, D and F had higher trypsin activity (p < 0.05). Group F had the tallest villi, Group B had the thickest muscular layer (p < 0.05), and villus width was similar among groups (p > 0.05). The experimental groups had fewer intestinal pathogenic bacteria, and Group F had improved intestinal microorganism diversity and richness (p < 0.05). In conclusion, adding 0.1% oligotriosaccharide and 0.2% brown algae powder enzymatic product to feed can promote largemouth bass growth, antioxidant capacity and immunity. The 0.2% brown algae powder enzymatic product is better for intestinal development and flora improvement.